Unity and objectivity in Strawson and Cassam - Gomes, A (Wiley, 2020)
Some comments on Quassim Cassam's Self and World written for a conference at the Institute of Philosophy in 2017. I consider the objection that Cassam raises to Strawson's argument from unity to objectivity in The Bounds of Sense and raise some general questions about Cassam's problem of misconception and its application to transcendental arguments.